2017
DOI: 10.1371/journal.pone.0179760
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary history and phylogeographic relationships of shrews from Sorex araneus group

Abstract: Shrews of the Sorex genus are an evolutionarily successful group that includes more than 77 species widely distributed in Eurasia and North America. The genus is one of the rare cases where karyotypic changes reflect well the evolutionary relationships among its species. The taxa showing the greatest variation in karyotype are usually classified into the Sorex araneus group. Its evolution was associated with chromosomal rearrangements, which could have promoted fast diversification of this group into many chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 75 publications
(129 reference statements)
4
20
1
Order By: Relevance
“…In Figure , the “araneus” group is placed as a well‐supported sister branch to S. samniticus , and the relationships within the former clade (Supporting Information Figure ) are the same as in previous studies (Bannikova & Lebedev, ; Fumagalli et al., ; Mackiewicz et al., ). The species of the “caecutiens” group do not form a clade; however, S. caecutiens clusters robustly with S .…”
Section: Resultssupporting
confidence: 61%
See 3 more Smart Citations
“…In Figure , the “araneus” group is placed as a well‐supported sister branch to S. samniticus , and the relationships within the former clade (Supporting Information Figure ) are the same as in previous studies (Bannikova & Lebedev, ; Fumagalli et al., ; Mackiewicz et al., ). The species of the “caecutiens” group do not form a clade; however, S. caecutiens clusters robustly with S .…”
Section: Resultssupporting
confidence: 61%
“…In the mitochondrial phylogenetic tree (Mackiewicz et al., ; our data), the basal lineage includes S . arcticus+S .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Our topology (see Figure ) was consistent with previous phylogenetic studies based on mtDNA, in which it has been suggested that S. granarius is closely related to S. araneus (Fumagalli, Hausser, Taberlet, Gielly, & Stewart, ; Taberlet, Fumagalli, & Hausser, ; Yannic, Basset, & Hausser, ,b). However, studies based on Y‐chromosomes and karyotypic data have argued that S. granarius occupies a basal position and should be considered the common ancestor of all species of the S. araneus complex (Yannic, Dubey, Hausser, & Basset, ; Mackiewicz, Moska, Wierzbicki, Gagat, & Mackiewicz, ). This phylogenetic inconsistency has been attributed to past mtDNA introgression from S. araneus to S. granarius (Yannic et al.…”
Section: Discussionmentioning
confidence: 99%